Effects of Tb doping on structural and electrical properties of 47(Ba0.7Ca0.3)TiO3–0.53Ba(Zr0.2Ti0.8)O3 thin films at various annealing temperature by pulsed laser deposition. Issue 6 (15th April 2018) - Lu, Haowei; Liu, Lizhu; Lin, Jiaqi; Yang, Wenlong; Weng, Ling; Zhang, Xiaorui
Abstract: The ceramic thin films of 47(Ba0.7 Ca0.3 )TiO3 –0.53Ba(Zr0.2 Ti0.8 )O3 (BCZT) + x ( x = 0.2, 0.3, 0.4 and 0.5) mol% Tb were grown on Pt(111)/Si substrates with various annealing temperature by pulsed laser deposition. The XRD spectra confirm that Tb element can enhance the (l10) and (111) orientations in ceramic films. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) images show that Tb-doping can increase particle size effectively. The surface of Tb-doped film annealed at 800 ℃ is uniform and crack-free, and the average particle size and mean square roughness (RMS) are about 280 nm and 4.4 nm, respectively. Comparing with pure BCZT, the residual polarization ( P r ) of 0.4 mol% Tb-doped film annealed at 800 ℃ increase from 3.6 to 9.8 μC/cm 2 . Moreover, the leakage current density value of Tb doped films are one order of magnitude (5.33 × 10 −9 −1.97 × 10 −8 A/cm 2 under 100 kV/cm) smaller than those of pure BCZT films (1.02 × 10 −7 A/cm 2 ).